Early childhood lower respiratory illness and air pollution - Hertz-Picciotto, Irva; Baker, Rebecca James; Yap, Poh-Sin; Dostál, Miroslav; Joad, Jesse P; Lipsett, Michael; Greenfield, Teri; Herr, Caroline E W; Benes, Ivan; Shumway, Robert H; Pinkerton, Kent E; Srám, Radim (Environmental health perspectives, 2007)
BACKGROUND: Few studies of air pollutants address morbidity in preschool children. In this study we evaluated bronchitis in children from two Czech districts: Teplice, with high ambient air pollution, and Prachatice, characterized by lower exposures. OBJECTIVES: Our goal was to examine rates of lower respiratory illnesses in preschool children in relation to ambient particles and hydrocarbons. METHODS: Air monitoring for particulate matter < 2.5 microm in diameter (PM(2.5)) and polycyclic aromatic hydrocarbons (PAHs) was conducted daily, every third day, or every sixth day. Children born May 1994 through December 1998 were followed to 3 or 4.5 years of age to ascertain illness diagnoses. Mothers completed questionnaires at birth and at follow-up regarding demographic, lifestyle, reproductive, and home environmental factors. Longitudinal multivariate repeated-measures analysis was used to quantify rate ratios for bronchitis and for total lower respiratory illnesses in 1,133 children. RESULTS: After adjustment for season, temperature, and other covariates, bronchitis rates increased with rising pollutant concentrations. Below 2 years of age, increments in 30-day averages of 100 ng/m(3) PAHs and of 25 microg/m(3) PM(2.5) resulted in rate ratios (RRs) for bronchitis of 1.29 [95 % confidence interval (CI), 1.07-1.54] and 1.30 (95% CI, 1.08-1.58), respectively; from 2 to 4.5 years of age, these RRs were 1.56 (95% CI, 1.22-2.00) and 1.23 (95% CI, 0.94-1.62), respectively. CONCLUSION: Ambient PAHs and fine particles were associated with early-life susceptibility to bronchitis. Associations were stronger for longer pollutant-averaging periods and, among children > 2 years of age, for PAHs compared with fine particles. Preschool-age children may be particularly vulnerable to air pollution-induced illnesses.
Keywords: Female; Pneumonia; Infant; Seasons; respiratory illness; Bronchiolitis; předškolní dítě; novorozenec; pneumonie; bronchitida; ženské pohlaví; PM2.5; PAHs; lidé; Infant, Newborn; Bronchitis; particulate matter; roční období; bronchiolitida; children’s health; kohortové studie; volatile organic compounds; Cohort Studies; retrospektivní studie; Male; Air Pollutants; kojenec; Czech Republic; polycyklické aromatické uhlovodíky; Child, Preschool; Polycyclic Aromatic Hydrocarbons; riziko; bronchitis; vystavení vlivu životního prostředí; Česká republika; air pollution; infant; mužské pohlaví; Risk; polycyclic aromatic hydrocarbons; látky znečišťující vzduch; Environmental Exposure; Retrospective Studies; Humans